Cutaneous angiofibroma: A clinching evidence for diagnostic workup of tuberous sclerosis complex - Bhushan M Warpe; Bhagyashree P Mundhe; Shweta Joshi-Warpe; Ashwini Kulkarni (Wolters Kluwer Medknow Publications, 2020)
Tuberous sclerosis complex (TSC) or Bourneville's disease is a genetic multisystem disorder of multisite hamartomas. Majority of TSC cases are sporadic. TSC typically presents in the first decade of life and has a reported incidence of 1:6000-12,000, with intracranial involvement in the form of cortical tubers or subependymal nodules. Tubers (potato-like nodules) are triangular-shaped lesions centered at the cortex/juxtacortical, with apex oriented "inward" toward the ventricles, on magnetic resonance imaging (MRI) of the brain. Tubers represent cortical glioneuronal hamartomas and consist of focal distortions in the cellular organization and morphology, which extend into the underlying (subcortical) white matter. Skin lesions with a history of seizures can be an eye-opener to diagnose angiofibromas and its variant, which can lead to further effective workup such as ophthalmoscopy and MRI of the brain to diagnose TSC, just like in our case.